Influence of pore structure characteristics on the Permian Shan-1 reservoir in Longdong, Southwest Ordos Basin, China - Xu Guangjun; Li Hao; Tang Lei; Gong Xiaoke; Xie Yuxin; Zhao Danni; Chen Jiangmeng; Wei Qinlian (Open Geosciences)
This study aims to characterize the pore structures and controlling factors of the Shan-1 Member reservoir in the southwestern Ordos Basin, a geological formation known for its significant gas production. Thin section analysis, scanning electron microscopy, high-pressure mercury intrusion (MICP), and reservoir physical property analysis were employed to investigate the pore structures within the reservoir. The Shan-1 Member reservoir is primarily characterized by lithic dissolution and intergranular pores, with generally small throat radii. Reservoirs with high quartz content (>70%) are associated with the development and preservation of primary pores, resulting in superior pore structures (Types I and II) with larger pore throats. Similarly, reservoirs with low lithic content (<10%) exhibit Type I and II pore structures, also with larger median pore throat radii. In contrast, Type III and IV pore structures, characterized by smaller median pore throat radii, are linked to higher lithic content. Compaction significantly degrades pore structures, while cementation and dissolution play key roles in controlling their variability. These processes underscore the complexity of the Shan-1 reservoir, with important implications for optimizing exploration strategies. This study provides novel insights into the interplay between mineral composition and diagenetic processes in shaping pore structures, offering valuable guidance for the exploration of tight gas reservoirs within the Permian strata of the southwestern Ordos Basin.